2016
DOI: 10.18235/0000508
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Validity and Feasibility of Short Tests Currently Used to Measure Early Childhood Development in Large Scale Studies: Methodology and Results

Abstract: work is licensed under a Creative Commons IGO 3.0 AttributionNonCommercial-NoDerivatives (CC-IGO BY-NC-ND 3.0 IGO) license (http://creativecommons.org/licenses/by-nc-nd/3.0/igo/ legalcode) and may be reproduced with attribution to the IDB and for any non-commercial purpose, as provided below. No derivative work is allowed.Any dispute related to the use of the works of the IDB that cannot be settled amicably shall be submitted to arbitration pursuant to the UNCITRAL rules. The use of the IDB's name for any purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
1
2
0
2
Order By: Relevance
“…The scores of the boys and girls of this Colombian sample showed that gross motor skills and fine motor skills showed the most risk; results that agreed with previous studies carried by Demestre et al 15 Ballantyne et al, 34 and Aakre et al 41 It is possible that this difference may be due to cultural differences, given that motor skills include various concepts, such as child independence 18 and social behaviours are culturally influenced. 17 In addition, it is possible to observe that when children are older, the mean scores rise, a similar tendency reported in studies by Steenis et al 42 and Rubio-Codina et al 8 given that they are correlated with a set of socio-economic variables (socio-economic level, educational level of the parents, and access to social security), and of the culture of the child and the mother (traditions, beliefs and customs related to the upbringing). To conclude, this study is a pioneer in Colombia in using a validated test widely used in European countries and the United States for child development screening.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The scores of the boys and girls of this Colombian sample showed that gross motor skills and fine motor skills showed the most risk; results that agreed with previous studies carried by Demestre et al 15 Ballantyne et al, 34 and Aakre et al 41 It is possible that this difference may be due to cultural differences, given that motor skills include various concepts, such as child independence 18 and social behaviours are culturally influenced. 17 In addition, it is possible to observe that when children are older, the mean scores rise, a similar tendency reported in studies by Steenis et al 42 and Rubio-Codina et al 8 given that they are correlated with a set of socio-economic variables (socio-economic level, educational level of the parents, and access to social security), and of the culture of the child and the mother (traditions, beliefs and customs related to the upbringing). To conclude, this study is a pioneer in Colombia in using a validated test widely used in European countries and the United States for child development screening.…”
Section: Discussionsupporting
confidence: 77%
“…Researchers and policy makers have emphasized the need to use instruments that report optimal psychometric characteristics, such as reliability and validity to obtain more precise and contextualised measurements regarding child development. 8 The ASQ-3 9 has proven to be a valid instrument for the evaluation of development, which can be easily administered by caregivers and previously trained personnel. 10 In addition, the ASQ-3 has been found to be accurate in identifying possible delays in development, because, in contrast with other tests, it targets observable abilities through structured and concrete questions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ASQ-3 (EE. UU) (11,12) validado en muchos países del mundo incluido Latinoamérica (13)(14)(15)(16)(17). A la fecha fue traducido a más de 65 idiomas (26).…”
Section: Resultsunclassified
“…), posee una buena confiabilidad mediante el análisis de consistencia interna, la validez de contenido y constructo son buenas, sensibilidad: 0,8, especificidad: 0,85 y los puntos de corte establecidos para los 21 cuestionarios (6,11,12). En Latinoamérica, la versión en español se encuentra validada en México (13), Brasil (14), Colombia (15), Chile (16) y Argentina (17).…”
Section: Introductionunclassified